Faktor Risiko Kejadian Diabetes Mellitus Tipe IiDi Wilayah Kerja Puskesmas PurwodiningratanSurakarta - Sukmaningsih, Wahyu Ratri; , Heru SubarisKasjono, SKM., M.Kes; , Kusuma Estu Werdani, SKM., M.Kes (2016)
Diabetes became one of the main causes of death in the world. Prevalence of type II diabetes in Puskesmas Purwodiningratan in 2014 (7,48%) was higher than the prevalence in 2012 (4,08%). This study aims to know the dominant risk factors associated with the incidence of Type II Diabetes Mellitus in Puskesmas Purwodiningratan Surakarta. This research is an observational study with case control approach. The population in this research are all people who suffer from type II diabetes and not suffer from type II diabetes. The selection of the sample using Fixed Disease Sampling technique to ensure sufficient number of research subjects that were taken from three villages with the highest case. Then for taking cases as much as 40 samples and control as much as 80 samples, used Proportionate Stratified Random Sampling technique. The bivariate analysis using Chi-square and multivariate analysis using logistic regression. The results of the bivariate analysis show that there is a relationship between a history of DM family (p = 0,006), there is a relationship between diets (p = 0,002), there is a relationship between physical activity (p = 0,000), and there is a relationship between smoking (p = 0,020) with the incidence of type II diabetes in Puskesmas Purwodiningratan Surakarta. Multivariate results showed that the value of OR of physical activity is highest, as much as 14,916 (95% CI = 4,663-47,715), it means that a person who has a low of physical activity amounting to 14,916 times of risk to experience the incidence of type II diabetes.